Social responsibility, consumption and production patterns in textile and cloth industry in Poland - Burchard-Dziubińska, Małgorzata (Economic and Environmental Studies, 2020)
The beginning of the systemic transformation was a period of structural challenge for Polish industry. In case of the textile industry it meant almost total collapse. Polish textile and clothing enterprises were supplanted by producers offering products of often poor quality, mainly from Asia. This paper presents results of research carried out in years 2014-2015 among young customers (up to 32 years of age), and entrepreneurs from textile and clothing industry in the Lodz voivodeship concerning the concept of social responsibility. The results of survey enable to formulate the conclusion, that the textile industry in Poland is able to meet the high standards of corporate social responsibility. Although it is still common practice in clothing industry to offer very low wages, labour in the informal economy and the lack of stable employment guarantees, it is possible to find factories operating in accordance with the CSR standards. However, young generation of customers shows little interest in socially responsible purchase of clothes, due to of lack of knowledge about social responsibility of producers and consumers. This attitude changes, if only customers become aware of the consequences of socially irresponsible behaviour of producers.